PENGARUH KESADARAN WAJIB PAJAK, KUALITAS PELAYANAN FISKUS, SANKSI PERPAJAKAN DAN LIGKUNGAN WAJIB PAJAK BERADA TERHADAP KEPATUHAN WAJIB PAJAK ORANG PRIBADI PADA KANTOR PELAYANAN PAJAK PRATAMA SEMARANG BARAT - Dewi Wahyu Lestari, 12.05.52.0038; Maryono, Maryono (Students Journal of Accounting and Banking, 2016)
This study examined the effect of taxpayer awareness , quality of service tax authorities, tax penalties , taxpayers and the environment are the Taxpayer Compliance in KPP Pratama Semarang Barat. This research was done in KPP Pratama Semarang Barat. Data were obtained from 99 respondents who are registered as individual taxpayer on KPP Pratama Semarang Barat. By using multiple linear regression techniques. the results showed that awareness of the Taxpayer, the quality of service tax authorities, tax penalties, and environmental Taxpayers are significant effect on the individual taxpayer compliance in Semarang.Keywords: Taxpayer Awareness, Quality Of Service Tax Authorities, Tax Sanction, Taxpayerâs Residency Environment